Pengembangan Website Layanan Bengkel Otomotif Dengan Integrasi Form Konsumen dan Sistem Admin Monitoring - Edo Panda Mesakh Silaban; Muhammad Heru Dwi Nugroho; Mokhammad Rifqi Tsani (Jurnal Manajemen Informatika & Teknologi, 2025)
Digital transformation in the automotive service sector is a strategic step to improve operational efficiency and customer satisfaction. This study aims to develop a website-based automotive workshop service integrated with a customer input form and an admin-based monitoring system to streamline service processes and operational management. The software development method used is the waterfall model, which includes requirements analysis, system design, implementation, testing, and maintenance. The website was developed using PHP, HTML, CSS, and MySQL database technology, supporting multi-user access for both customers and administrators. System testing was carried out using black-box testing and a usability test based on the System Usability Scale (SUS). The results show that all functions performed as expected and the usability score reached 82.5, indicating excellent user satisfaction. This website is expected to serve as an effective and efficient digital solution to support real-time workshop service management and enhance customer convenience in accessing automotive services.